A novel radiolabeled graft polymer: Investigation of the radiopharmaceutical potential using Albino Wistar rats - Avcibasi, Ugur; Ates, Buket; Unak, Perihan; Gumuser, Fikriye Gul; Gulcemal, Suleyman; Ol, Kevser Kusat; Akgol, Sinan; Tekin, Volkan (PERGAMON-ELSEVIER SCIENCE LTD, 2019)
Fe3O4 magnetic graft-Lys-poly(HEMA) was synthesized, labeled with Tc-99m for the first time and its radiopharmaceutical potential was investigated using animal models in this study. Quality control procedures were carried out using thin layer radiochromatography. The labeling yield of radiolabeled polymer was found to be about 100%. Then, stability and lipophilicity were determined. The lipophilicity of Tc-99m labeled Fe3O4 graft-Lys-poly(HEMA) was found to be 3.77. The serum stability experiments demonstrated that approximately 100% of radiolabeled polymer existed as an intact complex in the rat serum within 240 min. Biodistribution of radiolabeled magnetic graft-Lys-poly(HEMA) was performed on female Albino Wistar rats by scintigraphy and biodistribution studies. High uptake was seen in the stomach, the pancreas, brain, ovarian, intestines and the breast.
Keywords: HEMA; L-lysine; Grafted polymer; Nanoparticle; Tc-99m; IRON-OXIDE NANOPARTICLES; DRUG-DELIVERY-SYSTEM; MAGNETIC NANOPARTICLES; IN-VITRO; THERAPY; BIODISTRIBUTION; PACLITAXEL; MICROSPHERES; PROGRESS; Chemistry; Nuclear Science & Technology; Radiology, Nuclear Medicine & Medical Imaging